Deep Sea Mining in Social Sciences: A Systematic Review - Oztig, Lacin Idil (WILEY, 2025)
The effort to reduce carbon emissions and combat global warming has resulted in a significant increase in global demand for copper, cobalt, nickel and manganese, which are crucial components of electric vehicles, solar panels and wind turbines. The extraction of terrestrial mines is becoming increasingly problematic due to environmental challenges and human rights violations. Consequently, there is a growing interest in exploring deep sea mining (DSM) as a viable alternative source. The majority of literature on DSM originates from the disciplines of engineering, environmental science, earth and planetary sciences and agricultural and biological sciences. However, recent years have witnessed a greater focus on DSM in social science research. The objective of the present study is to perform a systematic review of social science articles on DSM. To accomplish this purpose, the screening of articles on DSM published between 1 January 2018 and 27 December 2024 was carried out using the SCOPUS database. Subsequent filters were applied to narrow down the results to include only social science articles. A total of 45 articles met the eligibility criteria. This study provides critical insights into the current landscape of social science research on DSM, shedding light on key aspects of the field. Although various studies address the political, legal, environmental and socio-economic dimensions of DSM, there is a notable absence of perspective from the international relations (IR) discipline. With the increasing relevance of DSM in global trade, politics and security, IR scholars have the unique opportunity to explore new dimensions of power dynamics related to the oceanic realm. This study identifies potential research trajectories in the context of regime theory, norm diffusion processes, spatial theorizing and interdisciplinary approaches that could be explored by IR scholars in the future.
Keywords: deep sea mining; international relations; social sciences; systematic review; NORMS; Development Studies